Smallholder farmer engagement in citizen science for varietal diversification enhances adaptive capacity and productivity in Bihar, India - Gotor, Elisabetta; Pagnani, Tiziana; Paliwal, Ambica; Scafetti, Flavia; Etten, Jacob van; Caracciolo, Francesco (Frontiers Media, 2021)
There is evidence that in many situations the use of a diverse set of two or more crop varieties in the field has benefits for production. The benefits of varietal diversification include lower crop disease incidence, higher productivity, and lower yield variability. Targeted interventions could increase varietal diversity where smallholder farmers lack the knowledge and access to seeds needed to diversify their varieties. Innovations based on crowdsourced citizen sciencemake it possible to involve a large number of households in farmer participatory varietal selection. This study analyses varietal diversification in Bihar, India, focusing on the effects of the largest citizen science-based intervention to date, involving 25,000 farmers and 47,000 plots ∗ seasons. The study examines if an increase in the varietal diversity of major staple crops, namely wheat and rice, under real farming conditions contributed to: (1) crop productivity and (2) the ability of households to recover from agricultural production shocks. We used the Rural Household Multi-Indicator Survey (RHoMIS) as a survey tool for rapid characterization of households and the sustainable rural livelihoods framework to understand the potential multiple interactions that are activated within the system by the intervention. We found that an increase in varietal diversification produced livelihood benefits in terms of crop productivity and the ability of households to recover from the occurrence agricultural shocks. Finally, outcomes highlight the effectiveness of development programmes aimed at strengthening rural livelihoods through participatory approaches and use of local crop varietal diversity.